Radiusfraktur: schneller beweglich mit zusätzlicher Mobilisation mit Bewegung - Vielitz, Arne (manuelletherapie, 2020)
Reid SA, Andersen JM, Vicenzino B. Adding Mobilisation with Movement to Exercise and Advice Hastens the Improvement in Range, Pain and Function after Non-Operative Cast Immobilisation for Distal Radius Fracture: a Multicentre, Randomised Trial. J Physiother 2020; 66: 105–112. doi:10.1016/j.jphys.2020.03.010